Rectal and sublingual administration of tacrolimus: a single-dose pharmacokinetic study in healthy volunteers - Stifft, Frank (Br J Clin Pharmacol, 2014)
AIMS: The immunosuppressant tacrolimus is usually administered orally. When this is not feasible, other routes of administration may be useful. Previous research suggested that tacrolimus may be applied sublingually or rectally. Pharmacokinetic data are sparse. The aim of this study was to investigate and compare the pharmacokinetics of these alternative formulations with orally administered tacrolimus. METHODS: Three single, fixed-dose formulations of tacrolimus were administered in a random sequence in 18 healthy subjects, using a cross-over study design. For sublingual administration, 3 mg of powder obtained from oral capsules was applied under the tongue for a period of 15 min without swallowing, with mouth rinsing afterwards. For rectal administration, a suppository containing 15 mg of the oral powder was used. Oral administration consisted of 7 mg of instant-release tacrolimus capsules (Prograf). Main pharmacokinetic outcome parameters were compared by anova. RESULTS: Sublingual administration showed no clinically significant exposure, contrary to rectal administration, where all subjects had clinically relevant exposure, with a lower relative bioavailability (78%), a lower maximal blood concentration and a later time of maximal blood concentration compared with oral administration. CONCLUSIONS: Sublingual administration of a single dose of tacrolimus does not result in systemic exposure if care is taken not to swallow saliva and to rinse the oral cavity afterwards. Rectal administration of tacrolimus results in clinically relevant systemic exposure and might represent an alternative formulation in case oral administration is not feasible. When used as a topical agent, systemic side-effects should be considered.